Implementasi Metode TOPSIS Fuzzy MADM dalam Seleksi Penerimaan Bidikmisi - Mei Dina Rahmi; Muhammad Subhan (Journal of Mathematics UNP, 2018)
Abstract – There are so many candidates and criterias in the process of Bidikmisi scolarship selection, but the awardees are limited. Therefore, we need an accurate method to gain precise decision. This research used Technique for Oder Preference by Similarity to Ideal Solution (TOPSIS) Fuzzy Multi Additive Decision Making (FMADM) method to Bidikmisi scolarhip selection. Bidikmisi scolarship selection in this research there are five criterias were determined, they are: parents income, life cost, the status of the house ownership, the land area, and the building area. The rating of the criteria have been done subjectively and objectively. Subjectively, the rating is gain from experts opinion and objectively the rating is gain from the result of TOPSIS. The output are the participants preference value. Based on the result of these research, the preference value are more accurate therefore only a few candidates have the same value. So this research proves that the ranking process have been done more carefully.